Pengembangan Media Mobile Learning Menggunakan Program Appy Pie Untuk Meningkatkan Hasil Belajar Mahasiswa - Muhammad Naharuddin Arsyad; Dinna Eka Graha Lestari (International Consortium of Education and Culture Research Studies, 2019)
The industrial revolution 4.0 is a trend in the industrial world that combines data exchange and automation technology. This trend changes human life in various fields including education. The use of this technology in education is still minimal , even though the instruments to implement it already exist. For example smartphone technology. Users of Android smartphones among students are very numerous. Therefore, the author took the initiative to develop and design an Android-based mobile learning media so that it was interesting by using an online builder program called